Kant and the reorientation of aesthetics - Tinguely, Joseph J.,Kant, Immanuel (Routledge, 2018)
Aside from beauty: the philosophical significance of Kantian aesthetics – Imagination: the productive imagination: an aesthetic touch – Tone: tone, modulation, and affectivity: the aesthetics of intentionality – Rhetoric: the implicit affection between Kantian judgment and Aristotelian rhetoric – Quarrels: Kantian quarrels: Hume, Rousseau, and the making of aesthetic discourse – Meta-aesthetics: Kantian meta-aesthetics and the neglected alternative – Orientation: orientation and the aesthetic symbolization of the world – Finding the world
9781138081970
Keywords: Kant; Immanuel; Aesthetics